Readiness for career affordances in high-level football: two case studies in Portugal - Sarmento, H.; Araújo, D. (High Ability Studies, 2020)
This study investigates the factors driving football players with identical training experience and genetics to have dramatically different career paths. We studied two paired cases from a pool of 32 talented U-20 players who were twice World Champions. The first paired case is a set of monozygotic twins that played football for exactly the same period of time yet only one of them was selected for the national team. The second paired case refers to an outstanding player who got injured and withdrew from his football career and the player who replaced him in the national team. Semi-structured interviews were conducted and then analyzed inductively. The results provide a description of opportunities (affordances) that could only be taken by those who were ready to act skillfully when such rare event occurred. To act on such affordances (or not) may dramatically change the outcome of a player`s career. These results suggest that expert performance and high achievement emerge from circumstances resulting from the self-organization of several performer-environmental factors. Acting on such opportunities (affordances) implies being perceptually attuned to and ready for unpredictable events. This research builds on the ecological dynamics approach and provides a basis for further understanding of expertise and expert performance.